Nilpotent orbits and codimension-2 defects of 6d N = (2, 0)theories - Chacaltana, Oscar [UNESP]; Distler, Jacques; Tachikawa, Yuji (World Scientific Publishing, 2013)
We study the local properties of a class of codimension-2 defects of the 6d N = (2, 0) theories of type J = A, D, E labeled by nilpotent orbits of a Lie algebra $g, where g is determined by J and the outer-automorphism twist around the defect. This class is a natural generalization of the defects of the six-dimensional (6d) theory of type SU(N) labeled by a Young diagram with N boxes. For any of these defects, we determine its contribution to the dimension of the Higgs branch, to the Coulomb branch operators and their scaling dimensions, to the four-dimensional (4d) central charges a and c and to the flavor central charge k. © 2013 World Scientific Publishing Company.
Keywords: defect operators; nilpotent orbits; Superconformal field theory